Features of Urea influence on physicochemical properties of working solutions of insecticides - О. Vlasova; M. Sekun; M. Zatserklyana (Карантин і захист рослин)
Goal. To study the effect of Urea on the properties of working solutions of emulsions and suspensions of chemical and microbiological drugs in plant protection against pests.